Sortion of Cytokines and Immunoglobulins in vitro with a New Carbon Hemosorbent: a Poster Study - V. A. Likholobov; T. I. Dolgikh; V. V. Moroz; L. G. Pyanova; V. T. Dolgikh; B. A. Reis; L. S. Luzyanina; F. I. Razgonov; T. F. Sokolova; A. V. Glushchenko; A. V. Veselovskaya (Общая реаниматология)
Objective: to study the specific features of sorption of some protein molecules (cytokines, immunoglobulins) in vitro, by using the carbon hemosorbent designed at the Institute of Hydrocarbon Process Problems, Siberian Branch, Russian Academy of Sciences.Materials and methods. 42 plasma samples from 14 patients with peritonitis were examined before and after hemosorption. Plasma was perfused through the hemosorbent with a plasma:hemosorbent ratio of 10:1 and a 5-cm3-column volume on an УНИРОЛ-1 at a rate of 15 ml/min.Results. The designed hemosorbent was found to absorb proinflammatory cytokines, such as tumor necrosis fac-tor-a and interleukin-1/J more than the hemosorbent VNIITU-1, and to significantly unchange the content of immunoglobulins M, G, and A. The absorptive capacity of the new hemosorbent was 48% greater than that of VNIITU-1.Conclusion. The findings may serve as a guide for further more in-depth studies of the specific features of sorption of plasma protein molecules from critically ill patients, by employingjust this carbon sorbent.